A goal model-driven supply chain design. (16th April 2009) - Chandra, Charu; Grabis, Janis
Modern decision-making problems are often characterised by a high degree of complexity and supply chain design is a good example of such a complex problem. In order to solve it, different problem-solving techniques, including descriptive modelling, quantitative modelling, computerised implementation and the presentation of results, should be considered. To achieve that, the goal model-driven supply chain design approach is proposed in this paper. This approach uses the principles of model- driven development to combine various problem-solving techniques. The paper describes the use of goal modelling to formally represent the supply chain design problem, defines transformations to obtain the multi-objective optimisation model on the basis of the goal model and uses business intelligence methods to represent modelling results. An example demonstrating the goal model-driven supply chain design is provided.